2022
DOI: 10.3390/ijerph19095726
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Contrasting the Impacts of Macro-Level Factors on Crash Duration and Frequency

Abstract: Road traffic crashes cause social, economic, physical and emotional losses. They also reduce operating speed and road capacity and increase delays, unreliability, and productivity losses. Previous crash duration research has concentrated on individual crashes, with the contributing elements extracted directly from the incident description and records. As a result, the explanatory variables were more regional, and the effects of broader macro-level factors were not investigated. This is in contrast to crash fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…In 2022, instead of using the variables extracted from incident descriptions and records, Chand et al collected explanatory factors at a macro-level and used latent class models to estimate the crash duration and frequency for unobserved heterogeneity. The results showed that income, driver experience, and exposure are considered to have both positive and negative impacts on duration [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, instead of using the variables extracted from incident descriptions and records, Chand et al collected explanatory factors at a macro-level and used latent class models to estimate the crash duration and frequency for unobserved heterogeneity. The results showed that income, driver experience, and exposure are considered to have both positive and negative impacts on duration [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such models are based on the assumption that the duration of a traffic incident can be predicted by a set of factors, including the incident type, time of day, and prevailing weather conditions, as well as the traffic volume. These models encompass widely used regression models [6][7][8][9][10], probabilistic statistical models [11][12][13], hazard-based models [14][15][16][17][18], copula-based models [19], finite mixture models [20,21], etc. They typically assume that the data follow a certain distribution and model and predict the distribution of the data.…”
Section: Statistical Approachmentioning
confidence: 99%
“…These factors include broader social, economic, and demographic conditions such as Gross Domestic Product (GDP), inflation rate, income levels, educational attainment, poverty rates, employment rates, average cost per mile traveled, daily vehicle miles traveled by drivers, and the extent of urban development in a particular area. Researchers have extensively studied these factors [5][6][7]. Previous studies have typically focused on individual contributing factors or a limited combination.…”
Section: Introductionmentioning
confidence: 99%